Caging Na3V2(PO4)2F3 Microcubes in Cross‐Linked Graphene Enabling Ultrafast Sodium Storage and Long‐Term Cycling - Cai, Yangsheng; Cao, Xinxin; Luo, Zhigao; Fang, Guozhao; Liu, Fei; Zhou, Jiang; Pan, Anqiang; Liang, Shuquan (Advanced science, 2018)
Sodium‐ion batteries are widely regarded as a promising supplement for lithium‐ion battery technology. However, it still suffers from some challenges, including low energy/power density and unsatisfactory cycling stability. Here, a cross‐linked graphene‐caged Na3V2(PO4)2F3 microcubes (NVPF@rGO) composite via a one‐pot hydrothermal strategy followed by freeze drying and heat treatment is reported. As a cathode for a sodium‐ion half‐cell, the NVPF@rGO delivers excellent cycling stability and rate capability, as well as good low temperature adaptability. The structural evolution during the repeated Na+ extraction/insertion and Na ions diffusion kinetics in the NVPF@rGO electrode are investigated. Importantly, a practicable sodium‐ion full‐cell is constructed using a NVPF@rGO cathode and a N‐doped carbon anode, which delivers outstanding cycling stability (95.1% capacity retention over 400 cycles at 10 C), as well as an exceptionally high energy density (291 Wh kg−1 at power density of 192 W kg−1). Such micro‐/nanoscale design and engineering strategies, as well as deeper understanding of the ion diffusion kinetics, may also be used to explore other micro‐/nanostructure materials to boost the performance of energy storage devices. A practical sodium‐ion full‐cell is constructed using a Na3V2(PO4)2F3@reduced graphene oxide cathode and a N‐doped carbon anode. It delivers outstanding cycling stability (95.1% capacity retention over 400 cycles at 10 C), as well as an exceptionally high energy density (291 Wh kg−1 at power density of 192 W kg−1).